Un fundamento filosófico para un modelo de sociedad culturalmente diversa - María del Carmen Gómez Martínez (Nóesis)
This article aims to outline some philosophical bases that allow support of a model of society that does not give up the ethnically and culturally richness that is in our country. The starting point is that cultural diversity is an obvious fact, but the models from the Modernity insisted on deleting an event such as cultural diversity for the sake of a single culture. The continuing struggle of ethnic and cultural groups respect their ways of life leads us to think it makes sense to insist on the creation of models of society to meet the needs of cultural diversity. This model is supported by two philosophical theses: relativity conceptual and ontological relativity.